ANALISIS KEAUSAN & KOEFISIEN GESEK MENGGUNAKAN TRIBOMETER PIN ON DISC PADA BAJA AISI C1045 DENGAN VARIASI KETEBALAN COATING DPRO NANO CERAMIC - Muchammad Sulthon Imaddudien; Althesa Androva, Aan Burhanuddin (ADISAM PUBLISHER, 2024)
A tribometer is a tool used to determine the condition of a material in the components of a machine so that the age of the component material I known. Pin on disc is a component tool used for tribometers, this tool is used as a tool to calculate wear and friction of the material being tested. Pin on disc tribology test equipment is a tool used to test friction and wear which is divided into pins and discs. This research aims to determine the war and friction coefficient of AISI C1045 steel against variations in coating thickness variation using a pin on disc tribometer. The highest wear value occurred in the 2 coating thickness variation experiment with a value of 76.73 gr/s.mm2, while the lowest wear value occurred in the variation without coating with a value of -19.13 gr/s.mm2. Furthermore, in the experiment, the highest coefficient of friction occurred in the 1 coating thickness variation with a value of 1.02, while the lowest coefficient value occurred in the variation without coating with a value of -0.2. The conclusion of this research is that the results of wear testing of specimens made from AISI steel show that variations in coating thickness affect the wear rate, where with 2 coating thickness variations the higher the wear value obtained compared to 3 variations.